Explosive Push-ups: From Popular Simple Exercises to Valid Tests for Upper-Body Power. Issue 10 (October 2020) - Zalleg, Dalenda; Ben Dhahbi, Anis; Dhahbi, Wissem; Sellami, Maha; Padulo, Johnny; Souaifi, Marouen; Bešlija, Tea; Chamari, Karim
Abstract : Abstract: Zalleg, D, Ben Dhahbi, A, Dhahbi, W, Sellami, M, Padulo, J, Souaifi, M, Bešlija, T, and Chamari, K. Explosive push-ups: From popular simple exercises to valid tests for upper-body power. J Strength Cond Res 34(10): 2877–2885, 2020—The purpose of this study was to assess the logical and ecological validity of 5 explosive push-up variations as a means of upper-body power assessment, using the factorial characterization of ground reaction force-based (GRF-based) parameter outputs. Thirty-seven highly active commando soldiers (age: 23.3 ± 1.5 years; body mass: 78.7 ± 9.7 kg; body height: 179.7 ± 4.3 cm) performed 3 trials of 5 variations of the explosive push-up in a randomized-counterbalanced order: (a) standard countermovement push-up, (b) standard squat push-up, (c) kneeling countermovement push-up, (d) kneeling squat push-up, and (e) drop-fall push-up. Vertical GRF was measured during these exercises using a portable force plate. The initial force-supported, peak-GRF and rate of force development during takeoff, flight time, impact force, and rate of force development impact on landing were measured. A significant relationship between initial force-supported and peak-GRF takeoff was observed for the countermovement push-up (CMP) exercises (standard countermovement push-up, kneeling countermovement push-up, and drop-fall push-up) and squat push-up (SP) exercises (standard squat push-up and kneeling squat push-up) ( r = 0.58 and r = 0.80, respectively; p < 0.01). Furthermore, initial force supported was also negatively correlated to a significant degree with flight time for both CMP and SP ( r = −0.74 and r = −0.80; p < 0.01, respectively). Principal component analysis (PCA) showed that the abovementioned 6 GRF-based variables resulted in the extraction of 3 significant components, which explained 88.9% of the total variance for CMP, and 2 significant components, which explained 71.0% of the total variance for SP exercises. In summary, the PCA model demonstrated a great predictive power in accounting for GRF-based parameters of explosive push-up exercises, allowing for stronger logical and ecological validity as tests of upper-body power. Furthermore, it is possible to adjust the intensity level of the push-up exercise by altering the starting position (i.e., standard vs. kneeling).